Real-world effectiveness of full and booster mRNA vaccination for coronavirus disease 2019 against disease severity during the delta- and omicron-dominant phases: A propensity score-matched cohort study using the nationwide registry data in Japan - Tetsuya Suzuki; Yusuke Asai; Shinya Tsuzuki; Hidetoshi Nomoto; Nobuaki Matsunaga; Eiichi N. Kodama; Kayoko Hayakawa; Norio Ohmagari (Journal of Microbiology, Immunology and Infection, 2024)
Background: To date, few studies from the Asian region have reported the effectiveness of messenger ribonucleic acid coronavirus disease 2019 (COVID-19) vaccines against disease progression and death after hospitalization. Methods: We evaluated the data from the COVID-19 registry in Japan during the delta- and omicron-dominant phases. A propensity score-matched cohort study was conducted between the incompletely (0–1 dose) and fully (2 doses) vaccinated groups during the delta-dominant phase and among the incompletely, fully, and booster (3 doses) vaccinated groups during the omicron-dominant phase. Results: In the delta-dominant phase, 411 pairs were matched. The fully vaccinated group showed a significantly lower oxygen supplementation rate (24.1 % vs. 41.1 %, p < 0.001) but little difference in the mortality rate (2.2 % vs. 2.9 %, p = 0.66). In the omicron-dominant phase, 1494 pairs from the incompletely and fully vaccinated groups, and 425 pairs from the fully and booster vaccinated groups were matched. Full vaccination reduced both the oxygen supplementation rate (18.6 % vs 25.7 %, p < 0.001) and mortality rate (0.7 % vs 2.3 %, p < 0.001). Booster vaccination showed little difference in either the rate of oxygen supplementation (21.2 % vs. 24.7 %, p = 0.25) or mortality (1.2 % vs. 2.6 %, p = 0.21) compared with full vaccination. Conclusions: Full vaccination reduced disease severity during the delta- and omicron-dominant phases; booster vaccination did not further enhance the protective effects against disease progression during the omicron-dominant phase compared to full vaccination. Future vaccine strategies and policy decisions should consider preventing infection or disease progression in the target population, as well as the characteristics of the dominant variant in that phase.